Sector approaches, sustainable livelihoods and rural poverty reduction - Gilling, Jim (2001)
Examines the relationship between sector-wide approaches (SWAps), sustainable livelihoods approaches (SLAs) and rural poverty reduction. Suggests that SLAs provide one means by which SWAps can focus more effectively on poverty reduction, whilst SWAps provide an entry point via which government and donor initiatives can be made supportive of the livelihoods of the poor. Provides guidelines indicating the core issues upon which donors should focus to enhance the poverty impact of sector-wide approaches.